PENGARUH PELATIHAN SUMBER DAYA MANUSIA DAN MOTIVASI KERJA KARYAWAN TERHADAP KREATIVITAS KARYAWAN UMKM PADA SAAT PANDEMI COVID-19 DI KABUPATEN KARAWANG - Ery Rosmawati; Wike Pertiwi (FEB Institut Bakti Nusantara, 2021)
Micro, Small and Medium Enterprises (MSMEs) are productive businesses that are individuals or business entities that have met the criteria as micro-enterprises, as regulated in legislation no. 20 of 2008. The relation with MSMEs, especially MSMEs in Karawang Regency which currently finds ± 87,574 (Ministry of UMKM and Cooperatives of Karawang Regency 2020), of the number of MSMEs 86% are engaged in food processing and only 14% are engaged in handicrafts . To make MSMEs have a product or service that has an appeal, a creativity that is owned by the leadership and employees. Especially in times of crisis, such as the Covid-19 pandemic. To foster high creativity in employees, training is needed to improve HR for MSME employees. In addition, to bring out creativity is training motivation. Motivation is an impulse that arises from within an individual to do the assigned task. The purpose of this study is to determine and explain the effect of human resource training and work motivation on the creativity of MSME employees. This study uses a quantitative approach. Respondents' data collection methods use literature studies and field surveys that have certain information on respondents so as to enable researchers to solve problems. This research has a high research urgency, especially in the field of Human Resources. Emphasizing on training and motivation where these variables are very supportive in increasing employee creativity. In this study, we found that Human Resource Training and Motivation had a positive and significant effect on Employee Creativity. It is evident from the two hypotheses that we accept, the results are accepted/supported. This means that it is important to conduct regular training for each employee, besides that employee creativity from the leadership also needs to be maintained so that employees are encouraged to increase creativity.